2013
DOI: 10.5433/1679-0359.2013v34n6p3069
|View full text |Cite
|
Sign up to set email alerts
|

Atividade de enzimas digestivas e parâmetros de crescimento de juvenis de jundiá (Rhamdia quelen) alimentados com farelo de linhaça in natura e demucilada

Abstract: This study was conducted out to evaluate the effect of partial replacement of animal protein (PBOA) for crude protein demucilaged linseed meal (PBFLD) and in nature (PBFL) ± 1.85 g) were reared in water recirculation system and fed to apparent satiation three times a day. At the end experimental parameters were evaluated for growth, carcass, chemical composition in whole fish and digestive enzymes. The fish fed control diet had best levels of feed conversion (p <0.05), however the remainder of the growth par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
0
16
0
3
Order By: Relevance
“…In studies with silver catfish juveniles of similar size, no significant differences were observed for these parameters either, but higher mean values of HSI (1.5 to 1.7%) and lower CY (84.3 to 86.4%) were obtained by Lovatto et al (2014) and Goulart et al (2013), respectively.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…In studies with silver catfish juveniles of similar size, no significant differences were observed for these parameters either, but higher mean values of HSI (1.5 to 1.7%) and lower CY (84.3 to 86.4%) were obtained by Lovatto et al (2014) and Goulart et al (2013), respectively.…”
Section: Resultsmentioning
confidence: 81%
“…Feed conversion (1.40 to 1.56) and specific growth rate (1.62 to 1.89%) were slightly worse than mean values of FC (1.3) and SGR (2.3%) presented by juveniles of R. quelen with initial weight of 14.5 g, fed different dietary levels of linseed for seven weeks (GOULART et al, 2013). However, the inferior results verified here might be related to a longer experimental period, which was almost twice longer than that of the aforementioned study.…”
Section: Resultsmentioning
confidence: 99%
“…The provision of diets containing up to 20% of HSM improved the growth of silver catfish without impairing food efficiency. Silver catfish is able to take advantage of different plant protein sources in the diet (Dalcin et al, ; Gourlat et al, ; Lovatto et al, ). High inclusion levels of plant protein sources in the diets leads to deficiency of essential amino acids and may compromise growth (Gatlin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mucilage was obtained from the grain of linseed in an aqueous medium at a 10% w/v concentration, at a temperature of 60 to 80°C with constant stirring, for 150 min, based on the methodology described by Goulart et al. (). Pectin was produced from citrus pulp in an aqueous medium under average temperature of 100°C, according to the methodology described by Calliari ().…”
Section: Methodsmentioning
confidence: 99%